Improvement of Shelf Life and Sensory Quality of Pummelos by Fruit Waxing and Wrapping - Aji, Titistyas Gusti; Susanto, Slamet; Sukma, Dewi; Ardie, Sintho Wahyuning (Journal of Tropical Crop Science, 2017)
The aims of this study were to evaluate the physical and chemical change of pummelo fruit during storage with waxing and wrapping, and to determine the effect of waxing and wrapping and their  its interaction in affecting shelf life of pummelo fruits. This research was arranged in a randomized complete block design with two factors and three replications. The first factor was waxing consisted of without waxing, 10% beeswax, 5% beeswax, and chitosan. The second factor was wrapping consisted of without wrapping and wrapping using either transparent yellow or white plastic wrap. Pummelo fruits experience weight loss, reduced total soluble solid (TSS), decrease in firmness and total acidity during 48 days of storage in room temperature. Waxing using beeswax or wrapping using plastic wraps significantly suppressed weight loss and maintained fruit firmness compared to those without waxing and wrapping. However, waxing and wrapping did not significantly affect the quality of pummelo fruits. Based on the fruit’s weight loss, firmness, and panelist preferences, 5% or 10% bees wax can be used as waxing. Both transparent yellow and white plastic wraps can be used to maintain fruit weight, firmness, and appearances during storage.